Caracterização de uma coleção de ossos contemporâneos conhecidos para o ensino/aprendizagem de osteologia e antropologia forense - Lopes, Allyson Rodrigo de Oliveira (2023)
Introduction: Collections are unique tools for various fields of knowledge, including paleopathology, paleomicrobiology, evolution, human anatomy and forensic anthropology. The recognition of human identification can be enriched by the existence of reference osteological collections. Among the numerous research methods, the questionnaire is one of the most suitable for obtaining significant data and results in a short period of time. Objective: The aim of this study was to characterize a collection of contemporary bones and to design and apply a questionnaire on knowledge of forensic osteology. Methodology: The sample studied belongs to the Contemporary Bone Collection of the Vitória Academic Center of the Federal University of Pernambuco. The study deals with estimating the effectiveness of the DSP version 2 tools for assessing sexual dimorphism using hip bones. To assess the importance of osteological knowledge for forensic anthropology, a questionnaire was drawn up with objective questions about anatomical knowledge of the skull and pelvis, related to sex determination. Results: Using the DSP2 tool, it was observed that it confers greater accuracy and reliability for females in the population studied. Theoretical and practical knowledge of forensic osteology helped the research participants learn. The participants' reports also corroborated the fact that practical knowledge of osteology helped in the practice of forensic anthropology. Problems in embryonic development and ageing can leave permanent marks on bone tissue. Conclusion: DSP2 helps to identify sexual dimorphism in forensic cases, even in populations with a high degree of miscegenation. Theoretical and practical classes equalize the learning opportunities for students with visuospatial abilities as an additional benefit in the practical class. There is little data on the prevalence of the cranial osteopathologies considered in this study in Brazilian populations.